Orthodontic uprighting of impacted mandibular permanent second molar: A case report - Reddy S; Uloopi K; Vinay C; Subba Reddy V (Wolters Kluwer Medknow Publications, 2008)
The mandibular second molars can become impacted beneath the crown of the first molars due to various causes and fail to erupt normally. Presented herewith is a case report of orthodontic uprighting of a mesioangular impacted mandibular right permanent second molar. Though various treatment options were available, an uprighting push spring appliance was used as it is easy to fabricate and produces distal tipping and uprighting of the impacted tooth without the necessity of surgical assistance, bone removal, or splinting. The uprighting of the mandibular second molar was achieved within two months.